Website Usability Evaluation of the Faculty of Education, Qasr Bin Ghashir - Samira M. Masoud Mansour; Salem Ramadan Salem Alwerfly; Assma Sharaf M. Etakasi; Salmah F. A. Alsagear; Ebrahem Ali Ebrahem Elburase (African Journal of Advanced Pure and Applied Sciences, 2026)
Nowadays, for educational organizations such as universities and higher institutions, the significance of a website for promoting their online services and communicating with their numerous clients (lecturers, researchers, students, staff, and guests) cannot be overemphasized. Website usability is the most significant factor in developing a high-quality website. This study aims to evaluate the usability and user experience of the Faculty of Education at Qaser Bin Ghashier (FOEQBG). Data was collected by utilizing the Website Analysis and Measurement Inventory (WAMMI) questionnaire, that measured website usability across five categories: Attractiveness, Controllability, Efficiency, Helpfulness, and Learnability. The responses were processed using SPSS. The study found that the FOEQBG performed well in terms of the Helpfulness sub-scale. However, users showed a fair or moderate satisfaction in terms of Attractiveness, Controllability, Efficiency, and Learnability. Thus, the overall usability fairly impacts the students’ academic experience and that of other users. As a result, the study’s recommendations were specified to identify areas for improvement to enhance user experience and satisfaction.